Wojciech Kossak a burżuazja łódzka - Klemantowicz, Dariusz (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2009)
Łódź before the First World War was one of biggest industrial centre on polish lands. It lived about 500 thousand person here. In 1914 there was 48,8% Poles, 26,6% Germans, 23,1% Jews, 0,9% Russians and 0,6% representatives of other nationalities. A bourgeoisie took active part in the economic, social and cultural life of the city. The bourgeoisie presented before 1914 about 3,2% whole of population. The multiethnic bourgeoisie predominated in Łódź and also tradesmen and workers. The cultural life not was one of the most important symptoms of the development of the city of Łódź. Wojciech Kossak liked better company of aristocracy, especially polish. He tolerated bourgeoisie in smallest degree. Łódź did not belong to cities which he admire. In the city of Łódź lived the families of the Scheiblers and Herbsts which Kossak respected.